Pilot- plant study for the photocatalytic/electrochemical degradation of Rhodamine B. Issue 2 (April 2018) - Baldisserri, Carlo; Ortelli, Simona; Blosi, Magda; Costa, Anna Luisa
Graphical abstract: Highlights: TiO2 -ceramized fabric used for the photocatalytic breakdown of Rhodamine B. Combined photocatalytic/electrochemical breakdown adding Pd-doped TiO2 /Ti anodes. 95% breakdown achieved in Na2 SO4 supporting electrolyte over three hours. CO3 2− and HCO3 − ions impair the photocatalytic performance of the ceramized fabric. Abstract: The combined photocatalytic/electrochemical breakdown performance of Rhodamine B dye in DI water and Na-based electrolytes was investigated in a 10 L semi-pilot flow reactor fitted with a Pd-doped TiO2 /Ti anode and a photocatalytic TiO2 ceramized fabric sleeve. The combined photocatalytic/electrochemical degradation performance was evaluated in Na2 CO3, (Na2 CO3  + NaCl), NaHCO3, and Na2 SO4 supporting electrolytes, and compared with that obtained by the electrochemical and photocatalytic processes alone. It was found that electrolytes containing CO3 2− and HCO3 − ions impair the photocatalytic performance of the TiO2 ceramized fabric, whereas the Na2 SO4 supporting electrolyte does not, thus allowing a synergetic action of the electrochemical and photocatalytic Rhodamine B degradation processes. Over three hours, 80% degradation efficiency was obtained in a NaHCO3 supporting electrolyte, while nearly 100% degradation efficiency was obtained in a Na2 SO4 supporting electrolyte. Under the electrochemical regime of this work (5 VDC cell potential and 3.2 A cell current), Rhodamine B degradation was exceedingly fast (∼100% in 1 h) in NaCl-containing electrolyte owing to electrochemical chlorination of the solution. Kinetics and process-related costs are also briefly discussed.